-2(a-5)=27-2a

Simple and best practice solution for -2(a-5)=27-2a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(a-5)=27-2a equation:


Simplifying
-2(a + -5) = 27 + -2a

Reorder the terms:
-2(-5 + a) = 27 + -2a
(-5 * -2 + a * -2) = 27 + -2a
(10 + -2a) = 27 + -2a

Add '2a' to each side of the equation.
10 + -2a + 2a = 27 + -2a + 2a

Combine like terms: -2a + 2a = 0
10 + 0 = 27 + -2a + 2a
10 = 27 + -2a + 2a

Combine like terms: -2a + 2a = 0
10 = 27 + 0
10 = 27

Solving
10 = 27

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 20(x-1)=-4(5-x)+16x | | y^2+11y-12=0 | | 12y^2-4y^4= | | 4x-2(x-7)=4 | | 6x^2+5x-8=-4 | | 43+63+57+4x=55 | | .18y+.04(y+6000)=1780 | | us+uz=t | | 7n=85n | | 2r-(-4+r)=7-2r | | 32y+5y=2 | | 6x-12+2x=7+8x-19 | | 7x+1x=3x+3 | | 5x(x)-13x+6=0 | | 2x+3(x+1)=13 | | 24x^2+76x+60=0 | | 3(2x-5y)=30 | | w-3=2w+5 | | -(3x+1)+2(1-2x)=-13 | | -5x-4=-2x+8 | | 2(3/8)= | | 61=6-8x-3 | | -10n+3(8+8n)=-6(m-4) | | (-19)-13= | | -4(2+3b)=8-4b | | -6(-8+v)=162 | | 1.5+4x=x+10 | | 7-3x+x=15 | | 16x^2+24x+7=0 | | 2t+10=4t+19 | | 15=5(4-7x) | | -5(3+q)+4=5q-11 |

Equations solver categories